2013
DOI: 10.1097/ncc.0b013e318291ba7d
|View full text |Cite
|
Sign up to set email alerts
|

The Tenacity and Tenuousness of Hope

Abstract: Understanding parental hope may assist healthcare professionals to avoid overloading parents with too much information at once. Healthcare professionals can also ensure that social support from family, community, and the medical center is available for parents and that their physical and emotional needs are being met to ensure that they maintain hope to best care for their child with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 16 publications
0
46
0
4
Order By: Relevance
“…Individuals sometimes make poor decisions if they do not have sufficient time to replenish self-regulation resources [36,37]. Parents of seriously ill children often report feeling physically and emotionally depleted [38] and may not have sufficient self-regulation resources to reevaluate their initial goals.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals sometimes make poor decisions if they do not have sufficient time to replenish self-regulation resources [36,37]. Parents of seriously ill children often report feeling physically and emotionally depleted [38] and may not have sufficient self-regulation resources to reevaluate their initial goals.…”
Section: Discussionmentioning
confidence: 99%
“…A child's uncertain life expectancy looms over those who love and care for them. There are multiple studies highlighting the importance of supporting children diagnosed with life-limiting (LLI) and/or life-threatening illnesses (LTI) and their parents' physical, emotional, cultural, spiritual, and psychosocial needs (Bally et al, 2014a; Barrera et al, 2013;O'Shea & Kanarek, 2013). However, research consistently identified that parents' needs are not being met and supportive interventions specific to this population are needed and limited in the current literature (Bally et al, 2014b;Rempel, Ravindran, Rogers, & Magill-Evans, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is not clearly understood how parents of children with lifethreatening or life-limiting conditions should be supported (O'Shea & Kanarek, 2013). A review of related literature about parental caregivers and supportive interventions revealed that caregivers repeatedly identified a lack of psychosocial support, but very few concrete interventions used to support caregivers are available (Bally et al, 2014a;Barrera et al, 2013;Revier, Meiers, & Herth, 2012). Many parental coping mechanisms have been qualitatively analyzed in research regarding caregivers' experiences and have provided important insight into potential psychosocial interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Social support can be thought of as a social ‘fund’ from which people may draw to help manage stressors (Thoits, 1995: 64), and research consistently finds that access to social support is an important factor in shaping families’ abilities to manage the stress associated with caring for a child with cancer (Fletcher, 2011; Hoekstra-Weebers et al, 2011; Manne et al, 2000; Rini et al, 2008; Trask et al, 2003; Wijnberg-Williams et al, 2006). For example, access to social support improves parents’ psychological and emotional resiliency throughout their child’s cancer therapy (Barrera et al, 2013; Greening & Stoppelbein 2007; Manne et al, 2000). Parents who have discussions about their child’s treatment with health care professionals feel they are better equipped to make decisions about their child’s care (Markward et al, 2013).…”
Section: Introductionmentioning
confidence: 99%